2005
DOI: 10.2131/jts.30.s39
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Generation Reproductive Toxicity Study of Butyl Benzyl Phthalate in Rats

Abstract: A two-generation reproductive toxicity study with extra parameters was performed for Butyl benzyl phthalate (BBP). The compound was administered orally by gavage with the doses of 0, 100, 200, or 400 mg/kg/day to groups of 24 Crj:CD (SD)IGS rats of both sexes to confirm the utility of the protocol for identification of non-steroid chemicals with endocrine activity by ssessing effects on parental animals and offspring. Softening of the testes, diffuse atrophy of testicular seminiferous tubules, decreased sperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Other authors have reported changes in the time of vaginal opening by prenatal plus prepubertal exposure to BBP by administration to the mothers of 1g/L in drinking water [27], as well as modifications in the anogenital distance of rats exposed prenatally by oral gavage to the pregnant dams with 100 mg BBP/kg body weight [28]. Another indicator of sexual maturity is the morphological and cellular changes of mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported changes in the time of vaginal opening by prenatal plus prepubertal exposure to BBP by administration to the mothers of 1g/L in drinking water [27], as well as modifications in the anogenital distance of rats exposed prenatally by oral gavage to the pregnant dams with 100 mg BBP/kg body weight [28]. Another indicator of sexual maturity is the morphological and cellular changes of mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that these studies did not consider litter effects, meaning their results may be affected by similarities between animals from the same litter. Other studies reported no change in the onset of sexual maturity using oral doses from 20 to 500 mg/kg/d in Sprague–Dawley rats (Aso et al, 2005; Nagao et al, 2000). The reasons for the contradictory results in these studies are difficult to resolve.…”
Section: Animal Studiesmentioning
confidence: 94%
“…Further, decreased ovarian weights were found in 500 mg/kg/d treated Sprague–Dawley rats (Nagao et al, 2000). BBP exposure (200 mg/kg/d orally) also decreased uterine weights in treated Sprague–Dawley rats (Aso et al, 2005). …”
Section: Animal Studiesmentioning
confidence: 98%
“…ECHA combined the LOAELs of 100 mg BBP/kg bw per day from the studies of Aso et al. () and Ahmad et al. (), and the NOAEL of 100 mg BBP/kg bw per day from the study of Nagao et al.…”
Section: Hazard Identification and Characterisationmentioning
confidence: 99%